Construction of biology critical thinking test of high school students - Taufiq Satria Mukti; Melly Elvira; Fantika Febry Puspitasari (JURNAL BIOEDUKATIKA, 2021)
Students must have various abilities, one of which is critical thinking skills. Critical thinking is an ability that is an indicator of successful learning and is directly related to real life. Should carry out the development of critical thinking skills effectively and efficiently in education. Critical thinking skills of students, accurate measurement tools are needed. The measuring instrument is in the form of a test instrument developed through research. Conduct the researched with a quantitative approach by describing the characteristics of the critical thinking test instrument. The research method was the development of a test with the research subjects of class X MIPA students from seven public high schools in Kendal Regency with the criteria of high, medium, and low ranking schools. Developed the test in the form of multiple-choice reasoned with three scoring categories for each item according to the scoring of the polytomous items in the PCM 1-PL model (Partial Credit Model 1 Parameter Logistic). The feasibility test of the critical thinking test instrument was carried out with experts in measurement, assessment, and Biology Learning and was tested empirically on 1118 students. The research data were analyzed using the EXCEL, SPSS 16, QUEST and PARSCALE applications. The results showed that: (1) The test instrument with four categories of scores fit the PCM 1-PL model; (2) the test instrument has a high-reliability value; (3) The test instrument has a right level of difficulty; (4) The test instrument can be used to measure the ability of students in the range of -3.7 to 2.9. The test instrument developed was feasible to be used to measure students' critical thinking skills with three categories of polytomous scoring with the PCM 1-PL model.